Continuous fiber reinforced high-performance PET (Polyethylene Terephthalate) material and preparation method thereof
Through continuous fiber-reinforced high-performance PET materials, combined with the synergistic effect of three-dimensional orthogonal braided fibers and interface treatment agents, the lack of mechanical and thermal properties of PET materials is solved, and the effects of high strength, impact resistance and anti-static are achieved, expanding its application range.
Patent Information
- Application Number
- CN202510691418.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-08-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing PET materials have shortcomings in terms of mechanical properties and thermal properties, poor toughness and impact resistance, insufficient heat resistance, and cannot be used stably under high stress and high temperature and high humidity environments, which limits its application range.
Using continuous fiber-reinforced high-performance PET materials, through the synergistic effect of three-dimensional orthogonal braided fibers and interface treatment agent composition, combined with the combination of hydrolysis stabilizer, nucleating agent and antistatic agent, three-stage pressurization and gradient cooling processes are used to prepare PET materials with high strength, impact resistance and antistatic functions.
It significantly improves the mechanical and thermal properties of PET materials, enhances the interface bonding between fibers and substrates, inhibits hydrolysis reactions in high-temperature and high-humidity environments, imparts antistatic functions to the material, and meets the needs of high-end applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PET materials, and in particular to a continuous fiber reinforced high-performance PET material and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) materials have been widely used in many fields due to their comprehensive performance. However, the defects of existing PET materials have significantly restricted their application expansion. First, there are limitations in mechanical properties, insufficient toughness and impact resistance, and more obvious brittleness after crystallization, which limits its application in high-stress scenarios and makes it difficult to meet industrial demands that have strict requirements on material strength and toughness. Second, its thermal performance is poor and its heat resistance is insufficient. It is easy to deform at around 70°C, and it will undergo hydrolysis reaction when in contact with water for a long time in a high temperature and high humidity environment, causing a sharp decline in mechanical properties, making it unable to adapt to complex high temperature and high humidity working conditions. In order to break through the above bottlenecks and improve the comprehensive performance of PET materials, the development of continuous fiber reinforced high-performance PET materials has become a key issue that needs to be solved urgently. It has important practical significance and application value for expanding the application field of PET materials and meeting high-end needs. Therefore, this application proposes a continuous fiber reinforced high-performance PET material and a preparation method. Summary of the Invention
[0003] The purpose of the present invention is to address the problem of poor mechanical and thermal properties of PET materials in the background technology, and to propose a continuous fiber reinforced high-performance PET material and a preparation method.
[0004] In a first aspect, the present application provides a continuous fiber reinforced high-performance PET material, comprising the following raw materials in parts by weight: 100 parts of PET resin, 30-65 parts of continuous fiber, 1.5-4.5 parts of hydrolysis stabilizer, 0.8-2.5 parts of nucleating agent, 2-6 parts of antistatic agent, 5-15 parts of interface treatment agent composition; Wherein, the continuous fiber is a three-dimensional orthogonal braided fiber with surface modification, and the interface treatment agent composition includes epoxy resin emulsion, silane coupling agent and nano-reinforced filler; The surface-modified three-dimensional orthogonal braided fibers are braided at 0° / 90° orthogonal layers, and the fibers are any one of carbon fibers, basalt fibers, and aramid fibers. The three-dimensional orthogonal braided structure is composed of interwoven fiber bundles in the X, Y, and Z directions, wherein the X and Y direction fibers are orthogonally arranged in the horizontal plane, and the Z direction fibers penetrate between layers perpendicular to the X / Y plane to form a three-dimensional interlocking network structure, wherein: The X-direction and Y-direction fibers are arranged orthogonally at an angle of 88°-92° in the horizontal plane, and the spacing between single-layer fiber bundles is 1-3 mm; The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 3-5 times / cm and an angle of 85°-89° with the horizontal plane; A gap of 0.2-0.5 mm is reserved between the X / Y fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume percentage of Z-direction fibers gradually changes from 10% in the surface layer to 25% in the core layer along the thickness direction; The fiber volume fraction is 30%-65%, and the single fiber diameter is 5-15 μm. The surface is treated as follows: a. ultrasonic cleaning with an acetone / ethanol mixture, followed by argon plasma activation treatment for 5-10 minutes; b. immersion in an interface treatment agent, which includes, by weight, 50-70 parts of an epoxy resin emulsion, 8-15 parts of γ-aminopropyltriethoxysilane, 5-10 parts of nano-boehmite, 3-8 parts of polyetheramine, and 0.5-3 parts of amino-graphene, at an immersion speed of 2-5 m / min; c. gradient drying and curing to obtain a surface-modified three-dimensional orthogonal braided fiber.
[0005] Optionally, the hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole UV absorber, and a polyetheramine in a weight ratio of (4-6):1:(0.5-2), and the molecular weight of the carbodiimide compound is 2000-5000 g / mol, and the carbodiimide compound is 3.4.5-trihalogen-2.6-diisopropylphenyl isocyanate.
[0006] Optionally, the antistatic agent is a composite of conductive carbon black and surface-silanized boron nitride nanosheets, the weight ratio of conductive carbon black to boron nitride is 1:(2-3), and the particle size of boron nitride is 50-200 nm.
[0007] Optionally, the interface treatment agent composition comprises: 55-70 parts of epoxy resin emulsion, 10-15 parts of γ-aminopropyltriethoxysilane, 6-10 parts of nano-boehmite, 3-8 parts of polyetheramine, and 0.5-3 parts of edge-aminated graphene nanosheets.
[0008] Optionally, the nucleating agent is a composite system of organic sodium phosphate and nano-calcium carbonate, with a weight ratio of (2-4):1.
[0009] Optionally, the particle size of the nano-calcium carbonate is 20-50 nm, and the surface is modified with stearic acid. The modification treatment specifically includes: taking 100 parts of nano-calcium carbonate, 3-8 parts of stearic acid, and 200-400 parts of ethanol solvent; adding the nano-calcium carbonate to ethanol and ultrasonically dispersing for 30 minutes (power 300 W); adding stearic acid, stirring at a constant temperature of 80-90°C for 2-4 hours (the pH value is adjusted to 8-9 with ammonia water); centrifuging and then washing with ethanol three times, and vacuum drying at 60°C for 12 hours.
[0010] In a second aspect, the present application provides a method for preparing a continuous fiber reinforced high-performance PET material as described in the first aspect, comprising the following steps: (1) Fiber surface treatment: immerse the continuous fiber bundle in the interface treatment agent composition at a speed of 2-5 m / min, control the glue amount to 3% to 8% of the fiber weight, and dry it at a gradient of 120-150℃ to form pretreated fibers; (2) Matrix premixing: melt-blend PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent in a twin-screw extruder to obtain modified PET matrix particles; (3) Lamination molding: alternately layer the pretreated fibers and the modified PET matrix film at 0° / 90°, insert a PET adhesive film containing 1-3 wt% ionic liquid between each layer, and perform three-stage pressurization in a vacuum hot press in sequence: the first stage: pre-pressing at 130-140℃ and 2-3 MPa pressure for 10-15 min; the second stage: pressurizing at 150-160℃ and 5-8 MPa pressure for 20-30 min; the third stage: final pressurizing at 165-175℃ and 8-10 MPa pressure for 5-10 min. min.
[0011] Optionally, the ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, which has a particle size of 50-200 nm and is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silicon dioxide composite shell layer with a wall thickness of 100-300 nm.
[0012] Optionally, in step (3), a gradient cooling process is used after lamination, specifically: The first stage: 165℃ to 120℃, cooling rate 2-5℃ / min; The second stage: 120℃ to 80℃, cooling rate 8-12℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
[0013] Optionally, the extrusion temperature of the twin-screw extruder is 260-280° C., and the screw speed is 200-400 rpm.
[0014] Compared with the prior art, this application has at least one of the following beneficial technical effects: Through the synergistic effect of the three-dimensional orthogonal woven fiber reinforcement structure and the interface treatment agent composition, the isotropic mechanical properties of the material are significantly improved, and the tensile strength, bending strength and impact resistance are significantly enhanced to meet the needs of high-stress scenarios.
[0015] The hydrolysis reaction in high temperature and high humidity environment is effectively inhibited by using hydrolysis stabilizers (multifunctional carbodiimides, etc.), and the crystallization efficiency is improved by combining with nucleating agents. The heat deformation temperature of the material is significantly increased, and the stability under high temperature conditions is enhanced.
[0016] The composite antistatic agent of conductive carbon black and silanized boron nitride nanosheets introduces thermal conductivity while reducing surface resistance. The interface treatment agent composed of epoxy resin emulsion, silane coupling agent and nanofiller (such as boehmite and amino graphene) greatly improves the fiber-matrix interface adhesion and reduces stress transfer loss through chemical bonding and physical anchoring.
[0017] The present invention adopts three-dimensional orthogonal woven fibers with surface modification, and is combined with an interface treatment agent composition composed of epoxy resin emulsion, silane coupling agent and nano-reinforced filler, and at the same time compounding specific proportions of hydrolysis stabilizers, nucleating agents, antistatic agents and other raw materials, combined with a three-stage pressurization and gradient cooling preparation process, to significantly improve the mechanical properties of PET materials, improve their thermal properties, effectively inhibit hydrolysis reactions in high temperature and high humidity environments, enhance the interfacial adhesion between the fibers and the matrix, and also give the material antistatic function. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0019] Example 1 The continuous fiber reinforced high-performance PET material comprises the following raw materials in parts by weight: 100 parts of PET resin and 30 parts of continuous fiber; 1.5 parts of a hydrolysis stabilizer, wherein the hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole UV absorber, and a polyetheramine in a weight ratio of 4:1:0.5, and the molecular weight of the carbodiimide compound is 2000 g / mol; 0.8 parts of a nucleating agent, which is a composite system of organic sodium phosphate and nano-calcium carbonate in a weight ratio of 2:1. The nano-calcium carbonate has a particle size of 20-50 nm and is surface-modified with stearic acid. 2 parts of antistatic agent, which is a composite of conductive carbon black and surface silanized boron nitride nanosheets, with a weight ratio of conductive carbon black to boron nitride of 1:2 and a boron nitride particle size of 50-200 nm; 5 parts of an interface treatment agent composition, comprising: 50 parts of an epoxy resin emulsion, 8 parts of γ-aminopropyltriethoxysilane, 5 parts of nanoboehmite, 3 parts of polyetheramine, and 0.5 parts of edge-aminated graphene nanosheets; The continuous fibers are surface-modified three-dimensional orthogonal woven fibers, which are made of basalt fibers woven in 0° / 90° orthogonal laminations, with a fiber volume fraction of 30% and a single fiber diameter of 5 μm.
[0020] The three-dimensional orthogonal braided structure is composed of interwoven fiber bundles in the X, Y, and Z directions. The X and Y fibers are arranged orthogonally in the horizontal plane, and the Z fibers run through the layers perpendicular to the X / Y plane, forming a three-dimensional interlocking network structure. In the three-dimensional interlocking network structure: The X- and Y-direction fibers are arranged orthogonally at an angle of 88° in the horizontal plane, with a spacing of 1mm between single-layer fiber bundles. The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 3 times / cm and an angle of 85° to the horizontal plane. A 0.2mm gap is reserved between the X / Y-direction fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume proportion of the Z-direction fibers gradually decreases along the thickness direction from 10% in the surface layer to 25% in the core layer. The preparation method of PET material comprises the following steps: (1) Fiber surface treatment: After ultrasonic cleaning with an acetone / ethanol mixture, the fiber was activated with argon plasma for 5 min. The continuous fiber bundle was then immersed in the interface treatment agent composition at a speed of 2 m / min. The amount of glue applied was controlled to be 3% of the fiber weight. The fiber was then dried and cured at 80°C, 120°C, and 150°C to form pretreated fibers. (2) Matrix premixing: PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent were melt-blended in a twin-screw extruder at an extrusion temperature of 260 °C and a screw speed of 200 rpm to obtain modified PET matrix particles; (3) Lamination: The pretreated fiber and the modified PET matrix film are alternately layered at 0° / 90°, and a PET adhesive film containing 1 wt% ionic liquid is inserted between each layer. The ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, and its particle size is 50-200 nm. It is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silica composite shell layer with a wall thickness of 100 nm. Three stages of pressurization are performed in a vacuum hot press in sequence: The first stage: pre-pressing at 130℃ and 2MPa pressure for 10min; The second stage: pressurization at 150°C and 5 MPa for 20 min; The third stage: final pressing at 165℃ and 8 MPa pressure for 5 min.
[0021] After lamination, a gradient cooling process is used, specifically: The first stage: 165℃ to 120℃, cooling rate 2℃ / min; The second stage: 120℃ to 80℃, cooling rate 8℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
[0022] Example 2 The continuous fiber reinforced high-performance PET material comprises the following raw materials in parts by weight: 100 parts of PET resin and 45 parts of continuous fiber; 2.5 parts of a hydrolysis stabilizer, wherein the hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole UV absorber, and a polyetheramine in a weight ratio of 5:1:1, and the molecular weight of the carbodiimide compound is 3500 g / mol; 1.2 parts of a nucleating agent, which is a composite system of organic sodium phosphate and nano-calcium carbonate in a weight ratio of 3:1. The nano-calcium carbonate has a particle size of 20-50 nm and is surface-modified with stearic acid. 3 parts of an antistatic agent, which is a composite of conductive carbon black and surface-silanized boron nitride nanosheets, with a weight ratio of conductive carbon black to boron nitride of 1:2.5 and a boron nitride particle size of 50-200 nm; 8 parts of an interface treatment agent composition, comprising: 60 parts of an epoxy resin emulsion, 10 parts of γ-aminopropyltriethoxysilane, 7 parts of nanoboehmite, 5 parts of a polyetheramine, and 1.5 parts of edge-aminated graphene nanosheets; The continuous fibers are surface-modified three-dimensional orthogonal woven fibers, which are woven from carbon fibers orthogonally stacked at 0° / 90°, with a fiber volume fraction of 30% and a single fiber diameter of 5 μm. The three-dimensional orthogonal woven structure is composed of interwoven X-, Y-, and Z-direction fiber bundles, wherein the X- and Y-direction fibers are arranged orthogonally in the horizontal plane, and the Z-direction fibers run through the layers perpendicular to the X / Y plane, forming a three-dimensional interlocking network structure. In the three-dimensional interlocking network structure: The X- and Y-direction fibers are arranged orthogonally at an angle of 89° in the horizontal plane, with a spacing of 1mm between single-layer fiber bundles. The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 3 times / cm and an angle of 86° to the horizontal plane. A 0.3mm gap is reserved between the X / Y-direction fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume proportion of the Z-direction fibers gradually decreases along the thickness direction from 10% in the surface layer to 25% in the core layer. The preparation method of PET material comprises the following steps: (1) Fiber surface treatment: After ultrasonic cleaning with an acetone / ethanol mixture, the fiber was activated with argon plasma for 8 min. The continuous fiber bundle was then immersed in the interface treatment agent composition at a speed of 3 m / min. The amount of glue applied was controlled to be 5% of the fiber weight. The fiber was then dried and cured at 80°C, 120°C, and 150°C to form pretreated fibers. (2) Matrix premixing: PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent were melt-blended in a twin-screw extruder at an extrusion temperature of 270 °C and a screw speed of 250 rpm to obtain modified PET matrix particles; (3) Lamination: The pretreated fiber and the modified PET matrix film are alternately layered at 0° / 90°, and a PET adhesive film containing 2 wt% ionic liquid is inserted between each layer. The ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, and its particle size is 50-200 nm. It is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silica composite shell layer with a wall thickness of 200 nm. Three stages of pressurization are performed in a vacuum hot press in sequence: The first stage: pre-pressing at 135°C and 2.5 MPa for 12 min; The second stage: pressurization at 154°C and 6 MPa for 22 min; The third stage: final pressing at 168°C and 9 MPa pressure for 6 min.
[0023] After lamination, a gradient cooling process is used, specifically: The first stage: 165℃ to 120℃, cooling rate 3℃ / min; The second stage: 120℃ to 80℃, cooling rate 9℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
[0024] Example 3 The continuous fiber reinforced high-performance PET material comprises the following raw materials in parts by weight: 100 parts of PET resin and 50 parts of continuous fiber; 3.5 parts of a hydrolysis stabilizer, wherein the hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole UV absorber, and a polyetheramine in a weight ratio of 5:1:1.5, and the molecular weight of the carbodiimide compound is 2000-5000 g / mol; 1.8 parts of a nucleating agent, which is a composite system of organic sodium phosphate and nano-calcium carbonate in a weight ratio of 3:1. The nano-calcium carbonate has a particle size of 20-50 nm and is surface-modified with stearic acid. 4 parts of an antistatic agent, which is a composite of conductive carbon black and surface-silanized boron nitride nanosheets, with a weight ratio of conductive carbon black to boron nitride of 1:2.5 and a boron nitride particle size of 50-200 nm; 10 parts of an interface treatment agent composition, comprising: 65 parts of an epoxy resin emulsion, 12 parts of γ-aminopropyltriethoxysilane, 8 parts of nanoboehmite, 6 parts of a polyetheramine, and 1.8 parts of edge-aminated graphene nanosheets; The continuous fibers are surface-modified three-dimensional orthogonal woven fibers, which are woven from carbon fibers orthogonally stacked at 0° / 90°, with a fiber volume fraction of 45% and a single filament diameter of 10 μm. The three-dimensional orthogonal woven structure is composed of interwoven X-, Y-, and Z-direction fiber bundles, wherein the X- and Y-direction fibers are arranged orthogonally in the horizontal plane, and the Z-direction fibers run perpendicular to the X / Y plane and through the interlayers, forming a three-dimensional interlocking network structure. In the three-dimensional interlocking network structure: The X- and Y-direction fibers are arranged orthogonally at a 90° angle in the horizontal plane, with a spacing of 2mm between single-layer fiber bundles. The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 4 times / cm and an angle of 87° to the horizontal plane. A 0.3mm gap is reserved between the X / Y-direction fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume proportion of the Z-direction fibers gradually decreases along the thickness direction from 10% in the surface layer to 25% in the core layer. The preparation method of PET material comprises the following steps: (1) Fiber surface treatment: After ultrasonic cleaning with an acetone / ethanol mixture, the fiber was activated with argon plasma for 10 min. The continuous fiber bundle was then immersed in the interface treatment agent composition at a speed of 3.5 m / min, with the amount of glue applied being controlled to be 5.5% of the fiber weight. The fiber was then dried and cured at 80°C, 120°C, and 150°C in a gradient drying process to form pretreated fibers. (2) Matrix premixing: PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent were melt-blended in a twin-screw extruder at an extrusion temperature of 270 °C and a screw speed of 300 rpm to obtain modified PET matrix particles; (3) Lamination: The pretreated fiber and the modified PET matrix film are alternately layered at 0° / 90°, and a PET adhesive film containing 2 wt% ionic liquid is inserted between each layer. The ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, and its particle size is 50-200 nm. It is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silica composite shell layer with a wall thickness of 200 nm. Three stages of pressurization are performed in a vacuum hot press in sequence: The first stage: pre-pressing at 135°C and 2.5 MPa for 12.5 min; The second stage: pressurization at 155°C and 6.5 MPa for 25 minutes; The third stage: final pressing at 170℃ and 9MPa pressure for 7.5 min.
[0025] After lamination, a gradient cooling process is used, specifically: The first stage: 165℃ to 120℃, cooling rate 3.5℃ / min; The second stage: 120℃ to 80℃, cooling rate 10℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
[0026] Example 4 The continuous fiber reinforced high-performance PET material comprises the following raw materials in parts by weight: 100 parts of PET resin and 60 parts of continuous fiber; 4 parts of a hydrolysis stabilizer, wherein the hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole UV absorber, and a polyetheramine in a weight ratio of 6:1:1.8, and the molecular weight of the carbodiimide compound is 4500 g / mol; 2.2 parts of a nucleating agent, which is a composite system of organic sodium phosphate and nano-calcium carbonate in a weight ratio of 3.8:1. The nano-calcium carbonate has a particle size of 20-50 nm and is surface-modified with stearic acid. 5 parts of an antistatic agent, which is a composite of conductive carbon black and surface-silanized boron nitride nanosheets, with a weight ratio of conductive carbon black to boron nitride of 1:2.8 and a boron nitride particle size of 50-200 nm; 13 parts of an interface treatment agent composition, comprising: 68 parts of an epoxy resin emulsion, 14 parts of γ-aminopropyltriethoxysilane, 9 parts of nanoboehmite, 7 parts of a polyetheramine, and 2.8 parts of edge-aminated graphene nanosheets; The continuous fibers are surface-modified three-dimensional orthogonal woven fibers, which are woven from aramid fibers at 0° / 90° orthogonal layers, with a fiber volume fraction of 65% and a single fiber diameter of 15 μm. The three-dimensional orthogonal woven structure is composed of interwoven X-, Y-, and Z-direction fiber bundles, wherein the X- and Y-direction fibers are arranged orthogonally in the horizontal plane, and the Z-direction fibers run perpendicular to the X / Y plane and through the interlayers, forming a three-dimensional interlocking network structure. In the three-dimensional interlocking network structure: The X- and Y-direction fibers are arranged orthogonally at a 91° angle in the horizontal plane, with a spacing of 2 mm between single-layer fiber bundles. The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 4 times / cm and an angle of 88° to the horizontal plane. A 0.4 mm gap is reserved between the X / Y-direction fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume proportion of the Z-direction fibers gradually decreases along the thickness direction from 10% in the surface layer to 25% in the core layer. The preparation method of PET material comprises the following steps: (1) Fiber surface treatment: After ultrasonic cleaning with an acetone / ethanol mixture, the fiber was activated with argon plasma for 10 min. The continuous fiber bundle was then immersed in the interface treatment agent composition at a speed of 4.5 m / min. The amount of glue applied was controlled to be 7% of the fiber weight. The fiber was then dried and cured at 80°C, 120°C, and 150°C to form pretreated fibers. (2) Matrix premixing: PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent were melt-blended in a twin-screw extruder at an extrusion temperature of 278 °C and a screw speed of 380 rpm to obtain modified PET matrix particles; (3) Lamination: The pretreated fiber and the modified PET matrix film are alternately layered at 0° / 90°, and a PET adhesive film containing 2.8 wt% of ionic liquid is inserted between each layer. The ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, and its particle size is 50-200 nm. It is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silica composite shell layer with a wall thickness of 260 nm. Three stages of pressurization are performed in a vacuum hot press in sequence: The first stage: pre-pressing at 138°C and 2.8 MPa for 14 minutes; The second stage: pressurization at 158°C and 7 MPa for 28 min; The third stage: 172℃, 9.5MPa pressure, final pressure for 9.5 min.
[0027] After lamination, a gradient cooling process is used, specifically: The first stage: 165℃ to 120℃, cooling rate 4.5℃ / min; The second stage: 120℃ to 80℃, cooling rate 11.5℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
[0028] Example 5 The continuous fiber reinforced high-performance PET material comprises the following raw materials in parts by weight: 100 parts of PET resin and 65 parts of continuous fiber; 4.5 parts of a hydrolysis stabilizer, wherein the hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole UV absorber, and a polyetheramine in a weight ratio of 6:1:2, and the molecular weight of the carbodiimide compound is 5000 g / mol; 2.5 parts of a nucleating agent, which is a composite system of organic sodium phosphate and nano-calcium carbonate in a weight ratio of 4:1. The nano-calcium carbonate has a particle size of 20-50 nm and is surface-modified with stearic acid. 6 parts of an antistatic agent, which is a composite of conductive carbon black and surface-silanized boron nitride nanosheets, with a weight ratio of conductive carbon black to boron nitride of 1:3 and a boron nitride particle size of 50-200 nm; 15 parts of an interface treatment agent composition, comprising: 70 parts of an epoxy resin emulsion, 15 parts of γ-aminopropyltriethoxysilane, 10 parts of nanoboehmite, 8 parts of a polyetheramine, and 3 parts of edge-aminated graphene nanosheets; The continuous fibers are surface-modified three-dimensional orthogonal woven fibers, which are woven from carbon fibers orthogonally stacked at 0° / 90°, with a fiber volume fraction of 65% and a single filament diameter of 15 μm. The three-dimensional orthogonal woven structure is composed of interwoven X-, Y-, and Z-direction fiber bundles, wherein the X- and Y-direction fibers are arranged orthogonally in the horizontal plane, and the Z-direction fibers run perpendicular to the X / Y plane and through the interlayers, forming a three-dimensional interlocking network structure. In the three-dimensional interlocking network structure: The X- and Y-direction fibers are arranged orthogonally at a 92° angle in the horizontal plane, with a spacing of 3 mm between single-layer fiber bundles. The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 5 times / cm and an angle of 89° to the horizontal plane. A 0.5 mm gap is reserved between the X / Y-direction fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume proportion of the Z-direction fibers gradually decreases along the thickness direction from 10% in the surface layer to 25% in the core layer. The preparation method of PET material comprises the following steps: (1) Fiber surface treatment: After ultrasonic cleaning with an acetone / ethanol mixture, the fiber was activated with argon plasma for 10 min. The continuous fiber bundle was then immersed in the interface treatment agent composition at a speed of 5 m / min. The amount of glue applied was controlled to be 8% of the fiber weight. The fiber was then dried and cured at 80°C, 120°C, and 150°C to form pretreated fibers. (2) Matrix premixing: PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent are melt-blended in a twin-screw extruder at an extrusion temperature of 280 °C and a screw speed of 400 rpm to obtain modified PET matrix particles; (3) Lamination: The pretreated fiber and the modified PET matrix film are alternately layered at 0° / 90°, and a PET adhesive film containing 3 wt% ionic liquid is inserted between each layer. The ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, and its particle size is 50-200 nm. It is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silica composite shell layer with a wall thickness of 300 nm. Three stages of pressurization are performed in a vacuum hot press in sequence: The first stage: pre-pressing at 140°C and 3 MPa for 15 min; The second stage: pressurization at 160°C and 8 MPa for 30 min; The third stage: final pressing at 175℃ and 10 MPa pressure for 10 min.
[0029] After lamination, a gradient cooling process is used, specifically: The first stage: 165℃ to 120℃, cooling rate 5℃ / min; The second stage: 120℃ to 80℃, cooling rate 12℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
[0030] Contrast ratio setting Comparative Example 1, raw materials: the same as Example 5, except that the interface treatment agent was replaced with a common silane coupling agent, 15 parts of γ-aminopropyltriethoxysilane; preparation method: the epoxy resin, nanoboehmite and graphene in the interface treatment agent were omitted, and only the silane coupling agent was used to treat the fiber.
[0031] Comparative Example 2, raw materials: the only difference from Example 5 is that only 6 parts of conductive carbon black are used as the antistatic agent; preparation method: the same as Example 5.
[0032] Comparative Example 3, raw materials: the only difference from Example 5 is that the nucleating agent is replaced by 2.5 parts of a single organic sodium phosphate; preparation method: the same as Example 5.
[0033] Comparative Example 4, raw materials: the only difference from Example 5 is that the interlayer adhesive film is a common PET film (without ionic liquid microcapsules); preparation method: the same as Example 5.
[0034] Comparative Example 5, raw materials: the only difference from Example 5 is that only 4.5 parts of carbodiimide compound (without benzotriazole and polyetheramine) is used as the hydrolysis stabilizer; preparation method: the same as Example 5.
[0035] Experimental verification plan 1. Mechanical properties test Test items: tensile strength (ASTM D638), notched impact strength (ASTM D256), interlaminar shear strength (ASTM D2344).
[0036] Comparison focus: Comparative Example 1 vs. Example 5: Verify the enhancement effect of nano-boehmite + graphene in the interface treatment agent on interface bonding.
[0037] Comparative Example 3 vs. Example 5: Verify the effect of the composite nucleating agent on crystallinity and low-temperature toughness.
[0038] 2. Thermal performance test Test items: heat deformation temperature (HDT, 1.82 MPa, ASTM D648), DSC analysis crystallization temperature (Tc).
[0039] Key points of comparison: Comparative Example 3 vs. Example 5: The effect of nano-calcium carbonate on increasing the crystallization temperature.
[0040] 3. Antistatic and wear resistance test Test items: volume resistivity (ASTM D257), friction coefficient (ASTM D1894), wear loss (load 50 N, speed 200 rpm, 1×10 6 cycles).
[0041] Comparison focus: Comparative Example 2 vs Example 5: Verify the synergistic effect of the compound of boron nitride and carbon black on antistatic stability and wear resistance.
[0042] Comparative Example 4 vs. Example 5: Verify the contribution of ionic liquid microcapsules to the self-lubricating performance.
[0043] 4. Heat and humidity aging test Test items: Tensile strength retention after aging for 1500h in 85℃ / 85%RH environment; Comparison focus: Comparative Example 5 vs. Example 5: Verification of the synergistic hydrolysis inhibition mechanism of polyetheramine and carbodiimide.
[0044] Experimental results and comparative analysis 1. Comparison of mechanical properties From the above data, we can find that: the interface treatment agent increases the interface shear strength by 78% (compared with comparative example 1), due to the dual effects of π-π stacking and chemical bonding of graphene; the composite nucleating agent (organic sodium phosphate + nano-calcium carbonate) increases the low-temperature impact strength by 37% (compared with comparative example 3), because nano-calcium carbonate inhibits grain coarsening.
[0045] 2. Comparison of thermal performance and antistatic properties From the data in the above table, it can be concluded that the compounding of boron nitride and carbon black reduces the resistivity by 2 orders of magnitude (compared with comparative example 2) and the friction coefficient by 42% (because the boron nitride layer blocks wear); the ionic liquid microcapsules reduce the friction coefficient by 46% (compared with comparative example 4) because a lubricating film is formed during the hot pressing process.
[0046] 3. Comparison of moisture and heat aging resistance From the above table, it can be seen that the combination of polyetheramine and carbodiimide increases the strength retention rate by 22% (compared with comparative example 5), because polyetheramine dynamically repairs broken chains (FTIR detects an 80% reduction in hydrolyzed carboxyl groups).
[0047] It is worth noting that in friction testing, Comparative Example 2 (carbon black only) exhibited a wear loss of 0.12 mm due to charge accumulation, while Example 5 exhibited a wear loss of only 0.04 mm, demonstrating that the boron nitride layer inhibits static charge accumulation through physical barrier and synergistic wear. The friction coefficient of Comparative Example 4 (no ionic liquid) increased continuously over time (0.41 → 0.55), while that of Example 5 remained stable at 0.22 ± 0.03, due to the microcapsules continuously releasing ionic liquid to repair the lubricating film. Comparative Example 3 (single nucleating agent) exhibited brittle fracture (grain size > 100 nm) upon impact at -40°C, while Example 5 exhibited ductile fracture (grain size ≤ 50 nm).
[0048] Comparative experiments have shown that the synergistic formula (interface treatment agent, composite antistatic agent, and nucleating agent compound) and process innovation (ionic liquid microcapsules and gradient cooling) of the present invention significantly improve the comprehensive performance of PET materials, especially achieving high strength and toughness, antistatic, self-lubrication and extreme environmental stability at the same time, breaking through the performance bottleneck of traditional reinforced PET.
[0049] The present invention adopts three-dimensional orthogonal woven fibers with surface modification, and is combined with an interface treatment agent composition composed of an epoxy resin emulsion, a silane coupling agent and a nano-reinforced filler, and at the same time compounding specific proportions of hydrolysis stabilizers, nucleating agents, antistatic agents and other raw materials, combined with a three-stage pressurization and gradient cooling preparation process, thereby significantly improving the mechanical properties of the PET material, improving its thermal properties, effectively inhibiting the hydrolysis reaction in a high temperature and high humidity environment, enhancing the interfacial adhesion between the fiber and the matrix, and giving the material antistatic and other functions. The preparation process can promote uniform and dense solidification of the material, reduce internal stress and defects, and is of great significance for expanding the application field of PET materials and meeting high-end needs.
[0050] The above specific embodiments are merely several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant inspirations of the above embodiments, those skilled in the art may make various alternative improvements and combinations to the above specific embodiments.
Claims
1. A continuous fiber reinforced high-performance PET material, characterized in that: It includes the following raw materials in parts by weight: 100 parts of PET resin, 30-65 parts of continuous fiber, 1.5-4.5 parts of hydrolysis stabilizer, 0.8-2.5 parts of nucleating agent, 2-6 parts of antistatic agent, 5-15 parts of interface treatment agent composition; Wherein, the continuous fiber is a three-dimensional orthogonal braided fiber with surface modification, and the interface treatment agent composition includes epoxy resin emulsion, silane coupling agent and nano-reinforced filler; The surface-modified three-dimensional orthogonal braided fibers are braided at 0° / 90° orthogonal layers, and the fibers are any one of carbon fibers, basalt fibers, and aramid fibers. The three-dimensional orthogonal braided structure is composed of interwoven fiber bundles in the X, Y, and Z directions, wherein the X and Y direction fibers are orthogonally arranged in the horizontal plane, and the Z direction fibers penetrate between layers perpendicular to the X / Y plane to form a three-dimensional interlocking network structure, wherein: The X-direction and Y-direction fibers are arranged orthogonally at an angle of 88°-92° in the horizontal plane, and the spacing between single-layer fiber bundles is 1-3 mm; The Z-direction fibers alternately penetrate adjacent X / Y-direction fiber layers in an "8"-shaped path, with an interlacing frequency of 3-5 times / cm and an angle of 85°-89° with the horizontal plane; A gap of 0.2-0.5 mm is reserved between the X / Y fiber layers to allow the Z-direction fibers to wrap around and form a mechanical interlocking structure. The volume percentage of Z-direction fibers gradually changes from 10% in the surface layer to 25% in the core layer along the thickness direction; The fiber volume fraction is 30%-65%, and the single fiber diameter is 5-15 μm. The surface is treated as follows: a. ultrasonic cleaning with an acetone / ethanol mixture, followed by argon plasma activation treatment for 5-10 minutes; b. immersion in an interface treatment agent, which includes, by weight, 50-70 parts of an epoxy resin emulsion, 8-15 parts of γ-aminopropyltriethoxysilane, 5-10 parts of nano-boehmite, 3-8 parts of polyetheramine, and 0.5-3 parts of amino-graphene, at an immersion speed of 2-5 m / min; c. gradient drying and curing to obtain a surface-modified three-dimensional orthogonal braided fiber.
2. The continuous fiber reinforced high performance PET material according to claim 1, characterized in that: The hydrolysis stabilizer is composed of a multifunctional carbodiimide compound, a benzotriazole ultraviolet absorber and a polyetheramine in a weight ratio of (4-6):1:(0.5-2), and the molecular weight of the carbodiimide compound is 2000-5000 g / mol.
3. The continuous fiber reinforced high performance PET material according to claim 1, characterized in that: The antistatic agent is a composite of conductive carbon black and surface silanized boron nitride nanosheets, the weight ratio of the conductive carbon black to the boron nitride is 1:(2-3), and the particle size of the boron nitride is 50-200 nm.
4. The continuous fiber reinforced high performance PET material according to claim 1, characterized in that: The interface treatment agent composition comprises: 55-70 parts of epoxy resin emulsion, 10-15 parts of gamma-aminopropyltriethoxysilane, 6-10 parts of nano-boehmite, 3-8 parts of polyetheramine, and 0.5-3 parts of edge-aminated graphene nanosheets.
5. The continuous fiber reinforced high performance PET material according to claim 1, characterized in that: The nucleating agent is a composite system of organic sodium phosphate and nano calcium carbonate, with a weight ratio of (2-4):
1.
6. The continuous fiber reinforced high-performance PET material according to claim 5, characterized in that: The particle size of the nano calcium carbonate is 20-50 nm, and the surface is modified with stearic acid.
7. A method for preparing a continuous fiber reinforced high-performance PET material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Fiber surface treatment: immerse the continuous fiber bundle in the interface treatment agent composition at a speed of 2-5 m / min, control the glue amount to 3% to 8% of the fiber weight, and dry it at a gradient of 120-150℃ to form pretreated fibers; (2) Matrix premixing: melt-blend PET resin, hydrolysis stabilizer, nucleating agent and antistatic agent in a twin-screw extruder to obtain modified PET matrix particles; (3) Lamination molding: alternately layer the pretreated fibers and the modified PET matrix film at 0° / 90°, insert a PET adhesive film containing 1-3 wt% ionic liquid between each layer, and perform three-stage pressurization in a vacuum hot press in sequence: the first stage: pre-pressing at 130-140℃ and 2-3 MPa pressure for 10-15 min; the second stage: pressurizing at 150-160℃ and 5-8 MPa pressure for 20-30 min; the third stage: final pressurizing at 165-175℃ and 8-10 MPa pressure for 5-10 min. min.
8. The method for preparing a continuous fiber reinforced high-performance PET material according to claim 7, characterized in that: The ionic liquid in the PET adhesive film is 1-butyl-3-methylimidazolium hexafluorophosphate, with a particle size of 50-200 nm, and is dispersed in the PET matrix in the form of microcapsules. The microcapsule wall material is a polyurethane-silicon dioxide composite shell layer with a wall thickness of 100-300 nm.
9. The method for preparing a continuous fiber reinforced high-performance PET material according to claim 7, characterized in that: In step (3), a gradient cooling process is used after lamination, specifically: The first stage: 165℃ to 120℃, cooling rate 2-5℃ / min; The second stage: 120℃ to 80℃, cooling rate 8-12℃ / min; The third stage: drop from 80℃ to room temperature and cool naturally.
10. The method for preparing a continuous fiber reinforced high-performance PET material according to claim 7, characterized in that: The extrusion temperature of the twin-screw extruder is 260-280°C, and the screw speed is 200-400 rpm.
Citation Information
Cited By
Compression-resistant PET plastic bottle composite material and preparation method thereof
CN121991474A